Disfunção do assoalho pélvico e qualidade de vida relacionada à saúde de gestantes - Soares, Paula Renata Amorim Lessa (2015)
Pregnancy can be construed as a period in which pelvic floor dysfunctions, such as urinary incontinence, anorectal conditions, sexual dysfunctions, pelvic organ prolapse, and pelvic floor denervation, may occur or worsen, negatively impacting quality of life among this specific female population. The research general objective was to analyze the influence of pelvic floor dysfunctions on the health-related quality of life (HRQoL) of pregnant women. It’s a cross-sectional, correlational, quantitative study which took place on four different environments: three public health unities and one private clinic. The study sample is composed of 261 pregnant women, 120 of them from the private clinic and 141 from the public health unit, who were interviewed from September to December of 2014.The instruments used were: a socio-demographic, obstetric and quality of life questionnaire; a questionnaire containing items related to urinary, fecal and pelvic organ prolapse symptoms; the Ferrans & Powers Quality of Life Index (adapted version); the King’s Health Questionnaire; the Jorge-Wexner Incontinence and Constipation Score; the Female Sexual Function Index (FSFI). The investigation of urinary symptoms in pregnancy showed a prevalence of polacyuria of 70.3% and 26.1% (68) had urinary incontinence, regardless of the type and term of pregnancy. Incontinent pregnant women felt more affected during the performance of daily activities, however, it can be said that, in general, UI caused little impact on the HRQoL of pregnant women. Regarding the symptom of AI and its interference in HRQoL of pregnant women, it was noted that this is a symptom with low prevalence with a percentage of 4.6% (12) and little impact on the HRQoL of women. Constipation, in turn, presented data slightly higher at 26.8% (70), but also had no impact on the HRQoL. The pelvic floor dysfunction with the highest prevalence of pregnant women was sexual dysfunction. The survey showed that 32.1% of participants have sexual dysfunction, with lower averages in the desire domain. It was also observed that pregnant women with sexual dysfunction had worse averages in the HRQoL than the ones without dysfunction. It can be concluded, therefore, that the HRQoL of pregnant women suffer negative influence from pelvic floor dysfunction. Thus, it is believed that this research has helped identify the impact of pelvic floor dysfunction on the HRQoL of pregnant women, indicating the main aspects that can be incorporated into prenatal care by health professionals, especially the nurses, in order to improve the HRQoL of pregnant women.